Concurrent nociceptive stimulation impairs the anxiolytic effect of midazolam injected into the periaqueductal gray in mice - Mendes-Gomes, J.; Nunes-de-Souza, R. L. (Elsevier B.V., 2005)
This study investigated whether the opportunity to avoid or escape the open arms of an elevated plus-maze (EPM) affects the antinociceptive response observed when mice are subjected to open arm confinement. Furthermore, in order to better characterize the relationship between emotion and antinociception in the EPM, we examined the behavioral effects of midazolam injection into the midbrain periaqueductal gray matter (PAG). As our main aim was to evaluate the relevance of different levels of approach-avoid conflict (i.e. The presence of open and closed arms) to maze-induced antinociception, mice were exposed to one of three types of EPM-a standard EPM (sEPM), an open EPM (oEPM: four open arms) or, as a control condition, an enclosed EPM (eEPM: four enclosed arms). Nociception was assessed using the formalin test. Twenty minutes after formalin injection (50 mu l, 2.5% formalin) into the dorsal right hind paw, mice received an intra-PAG injection of saline or midazolam (10-20 nmol). Five minutes later, they were individually exposed to one of the mazes for 10 min (25-35 min after formalin injection). Videotapes of the test sessions were scored for a variety of behavioral measures including time spent licking the formalin-injected paw. To examine whether the effects of midazolam on anxiety-like behavior may have been influenced by concurrent nociceptive stimulation (i.e. formalin pretreatment), naive mice were submitted to a similar procedure to that described above for the sEPM test but without formalin pretreatment. Results showed that mice exposed to the oEPM spent significantly less time licking the injected paw compared to groups exposed to either the sEPM or eEPM. Although exposure to the sEPM induced anxiety-like behaviors (i.e. open arm avoidance), it did not result in antinociception. Intra-PAG infusions of midazolam failed to block oEPM-induced antinociception or to alter sEPM-induced anxiety in mice that had received formalin injection. However, under normal test conditions (i.e. in the absence of formalin-induced nociceptive stimulation), intra-PAG midazolam produced clear anti-anxiety effects in mice exposed to the sEPM. Findings are discussed in terms of different emotional states induced by the oEPM and sEPM and the influence of concurrent nociceptive stimulation on the anti-anxiety effect of intra-PAG midazolam. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: anxiety; fear; different EPM; antinociception; midazolam; periaqueductal gray; mice